Linking leaf traits to growth responses under climate warming in tropical trees - Gardner, Anna; González-Caro, Sebastián; Dusenge, Mirindi Eric; Restrepo Correa, Zorayda; Hartley, Iain P.; Meir, Patrick; Mercado, Lina M. (Frontiers in Plant Science, 2025)
Climate warming is affecting the composition and distribution of Andean tropical montane forests (TMFs), resulting in varied growth responses among tree species. However, the underlying mechanisms driving these growth responses to climate warming remain largely unexplored. To address this knowledge gap, we investigated the role of leaf functional traits in mediating growth responses to temperature using a common garden experiment across a 2000 m thermosequence in the Colombian Andes. Fifteen dominant Andean tree species—originating from lowland and montane habitats—were grown under common soil and water conditions at three elevations. This experimental design exposed montane and lowland species to their native thermal environments as well as to warming and cooling respectively, thereby simulating upward migration consistent with documented shifts along elevation gradients. We measured 19 traits related to photosynthesis and its temperature response, thermotolerance, leaf structure and water use and assessed their associations with relative growth rates under warming and cooling conditions. Trait-growth relationships varied with thermal context. Thermal tolerance, photosynthesis and its temperature response, water use and leaf structural traits were consistently linked to growth explaining 88-91% of its variability across most thermal environments. However, for montane species under warming conditions, only thermal tolerance and photosynthetic traits remained significant, explaining 48% of the observed growth variability. Thermal acclimation of traits played an important role in mediating growth responses to temperature change. Traits associated with growth did not differ between species groups under native conditions but diverged under altered thermal environments. Collectively, these findings suggest that traits related to alternative physiological processes become increasingly relevant for montane tree species under climate warming. Our findings demonstrate that climate warming alters trait-growth relationships and highlights key functional traits that mediate growth responses to temperature.